STUDENT’S DIFFICULTY IN LISTENING WESTERN MOVIE - Fitri Widya Jayanti Hasibuan; Yani Lubis (University of Kuningan, 2024)
This research investigates the challenges students face in understanding Western films, focusing on language and dialect differences, narrative complexity, and cultural factors. Using a qualitative descriptive approach, data was collected through observation and interviews with students at SMP N 4 Sei Kanan. Findings indicate that language barriers, including unfamiliar accents and slang, complex plot structures with intricate storylines and character developments, and cultural nuances, such as differing social norms and historical references, pose significant difficulties for students. Additionally, students often struggle with idiomatic expressions and humor that do not translate well across cultures. This study suggests incorporating strategies to improve students' listening skills and cultural awareness through targeted educational interventions, such as integrating multimedia resources in the curriculum, conducting workshops on cultural contexts, and providing supplementary language support. By addressing these challenges, educators can enhance students' comprehension and appreciation of Western films, fostering a more inclusive and effective learning environments.Student Difficulties, Western Films, Language and Dialect Differences